Molecular Epidemiology and Prevalence of Macrolide Efflux Genes mef(A) and mef(E) in Streptococcus pneumoniae Obtained in Canada from 1997 to 2002 - Wierzbowski, Aleksandra K. (Antimicrob Agents Chemother, 2005)
One hundred forty M phenotype Streptococcus pneumoniae isolates were evaluated by PCR-restriction fragment length polymorphism, serotyping, and pulsed-field gel electrophoresis. Molecular genotyping revealed that the predominant macrolide resistance mechanism in S. pneumoniae in Canada is mef(E) and resistance dissemination is due to both spread of the genetic element MEGA as well as clonal dissemination of penicillin- and/or macrolide-resistant strains.